A high-hardness scratch-resistant tile and its preparation process
By using raw materials such as kaolin, quartz, potassium feldspar and modified mullite whiskers, combined with micro-nano glass powder and high-temperature sintering technology, the problem of easy scratches in ceramic tiles is solved, and the high hardness and scratch resistance are improved.
Patent Information
- Application Number
- CN202411076158.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Ceramic tiles are prone to defects such as scratches during use, which affects their aesthetics and service life.
High-hardness anti-scratch tiles are prepared by using raw materials such as kaolin, quartz, potassium feldspar and modified mullite whiskers. After wet ball milling and modification treatment, combined with micro-nanoglass powder, high-temperature sintering technology is used to prepare high-hardness anti-scratch tiles.
It improves the hardness and wear resistance of ceramic tiles, enhances its scratch resistance, and avoids the problem of tiles' strength decline caused by the increase in quartz phase.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tile processing, in particular to a high-hardness scratch-resistant tile and a preparation process thereof. Background Art
[0002] As a type of ceramic, tiles have long been part of the lives of thousands of households. Compared with ordinary cement tiles, marble floor tiles, etc., tiles have better anti-freeze and anti-fouling, water vapor erosion and chemical corrosion resistance, and are easy to clean; however, during use, due to the influence of factors such as dust and impurities in nature, tiles will inevitably have scratches and other defects during use, affecting the appearance and service life of the tiles. Summary of the invention
[0003] The object of the present invention is to provide a high-hardness scratch-resistant tile and a preparation process thereof to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A high-hardness anti-scratch ceramic tile, having the following technical features: by weight, the high-hardness anti-scratch ceramic tile is composed of 45-55 parts of kaolin, 5-12 parts of calcined high-alumina powder, 10-15 parts of quartz, 20-23 parts of potassium feldspar, 15-25 parts of modified mullite whiskers, and 0.15-0.4 parts of polyvinyl alcohol;
[0005] Wherein, the preparation method of the modified mullite whisker is:
[0006] a. The mullite whiskers were washed 3-5 times with deionized water, dried to constant weight, placed in a planetary ball mill, and the ball-to-material ratio was (8-12): 1. After ball milling for 5 minutes, the milled mullite whiskers were separated and dispersed in a sodium hydroxide solution, heated to 95°C, and ultrasonically reacted for 90-150 minutes. The mullite whiskers were centrifuged and washed 3-5 times with boiling deionized water. The mullite whiskers were dispersed again in KH550 at a solid-liquid ratio of 1: (10-25), heated to 75-85°C, ultrasonically dispersed for 0.5-1h, and 20% of the volume of KH550 deionized water was added thereto. After stirring the reaction for 2-5h, the mullite whiskers were centrifuged and vacuum dried to constant weight to obtain pre-treated mullite whiskers;
[0007] b. Place the micro-nano glass powder in a planetary ball mill, according to a ball-to-material ratio of (15-20): 1, ball milling for 10-15 minutes, separate the activated micro-nano glass powder after grinding, place it in KH560, the solid-liquid ratio is 1: (5-15), heat it to 75-85 ° C, ultrasonically disperse it for 0.5-1.5 hours, add 20% of the volume of KH560 deionized water, continue stirring the reaction for 2-4 hours, centrifuge the micro-nano glass powder, and vacuum evaporate it to constant weight to obtain pre-treated micro-nano glass powder;
[0008] c. Disperse the pretreated mullite whiskers into deionized water with a solid-liquid ratio of 1:(5-10), stir and mix for 15-25 minutes, add the pretreated micro-nano glass powder, stir and ultrasonically vibrate for 0.5-1h, heat to 85-95°C, stir and react for 0.5-1.5h, spray dry, collect the dried product, and obtain modified mullite whiskers.
[0009] Furthermore, in step a, the mullite whisker has a diameter of 0.2-3 μm and a length of 5-200 μm.
[0010] Furthermore, in step a, the pH value of the sodium hydroxide solution is 11.5-12; the solid-liquid ratio of the mullite whisker to the sodium hydroxide solution is 1:(8-50).
[0011] Furthermore, in step b, the particle size of the micro-nano glass powder is 1500-8000 mesh.
[0012] Furthermore, in step c, the mass ratio of the pre-treated mullite whiskers to the pre-treated micro-nano glass powder is 10:(2-4).
[0013] Furthermore, a method for preparing high-hardness scratch-resistant ceramic tiles comprises the following steps:
[0014] S1. Wet-mill kaolin, calcined high-alumina powder, quartz and potassium feldspar in a ball mill to remove iron. After passing through a 120-200 sieve, mix the milled raw materials, add modified mullite whiskers and polyvinyl alcohol, and continue to ball-mill for 0.5 h at a ball-to-material ratio of 10:1. Separate the ground slurry and dry it in an environment of 105±5°C until the water content in the slurry drops to 5-10%;
[0015] S2. The dried raw material was stirred and mixed again at a rate of 50-200rpm for 0.5-1h, and then the raw material was evenly sprayed with atomized deionized water 3-5 times. After the spraying, the raw material was left to stand for 4-8h;
[0016] S3. After the aged raw materials are pressed into shape, the green body is placed in a mold, the temperature is raised to 105-110°C while maintaining the pressure, and after drying at this temperature for 1-2 hours, the dried green body is transferred to a calcining furnace and calcined to obtain high-hardness scratch-resistant tiles.
[0017] Furthermore, in step S2, the total amount of the atomized deionized water is 5-8% of the mass of the raw material after drying.
[0018] Further, in step S3, the pressing pressure is 10-15 MPa;
[0019] Maintain the pressure and raise the temperature to 12-15MPa.
[0020] Furthermore, in step S3, when the green body is calcined after drying, the parameters are as follows:
[0021] The green body is heated to 850-900°C at a rate of 1.5-3°C / min, kept warm for 20-30min, then heated to 1150-1200°C, kept warm for 40-60min, heated to 1300-1350°C again, kept warm for 13-16h, cooled to 750-800°C at a rate of 0.5°C / min, kept warm for 30-70min, cooled to 400-500°C at a rate of 0.5°C / min again, kept warm for 30-40min, cooled to room temperature along with the furnace temperature, and the calcination is completed.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] In order to increase the hardness and wear resistance of ceramic tiles, the present invention uses kaolin and quartz as raw materials, supplemented with potassium feldspar, and sintered together to prepare high-hardness scratch-resistant ceramics, which contain more quartz phases and thus have relatively excellent hardness and scratch resistance. However, although the increase in quartz phases helps to increase the scratch resistance of ceramics, it will also cause the strength of ceramic tiles to decrease, and thus make the ceramic tiles easy to break. Therefore, on this basis, the present invention adds mullite whiskers to the raw materials. Although mullite whiskers have an extremely high aspect ratio, they are ridge materials like quartz materials. Simply adding mullite whiskers will make the bonding strength of mullite whiskers in ceramic materials insufficient and even cause problems such as cracking and breaking of ceramic tiles. Therefore, the present invention also modifies the mullite whiskers.
[0024] The present invention first immerses mullite whiskers in sodium hydroxide. Under high temperature heating, the sodium hydroxide dissolves the silicon phase in the mullite, thereby exposing the aluminum phase on the surface of the mullite whiskers. Then, the mullite whiskers are mixed with KH550 and amino groups are introduced on the surface of the mullite after hydrolysis.
[0025] On this basis, the present invention further uses micro-nano glass powder and KH560 to mix, introduces epoxy groups on the surface of the micro-nano glass powder after hydrolysis, and then mixes the pre-treated mullite whiskers with the pre-treated micro-nano glass powder. Under the action of epoxy groups and amino groups, part of the micro-nano glass powder will adhere to the surface of the mullite whiskers. Under the action of high temperature, the micro-nano glass powder will first melt to achieve the bonding between the mullite whiskers and the remaining ceramic materials. In addition, the micro-nano glass powder contains a large amount of silicon elements, which can react with the aluminum elements exposed on the surface of the mullite whiskers at high temperatures to generate a mullite structure again, further increasing the bonding strength of the mullite whiskers in the ceramic material and enhancing the mechanical properties of the ceramic. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The mullite whiskers used in the present application are ZX-MW-01 mullite whiskers; the micro-nano glass powder used is Anmi Micro-nano T801 glass powder.
[0028] Embodiment 1. A method for preparing a high-hardness scratch-resistant tile comprises the following steps:
[0029] S1. According to the weight percentage, 50 parts of kaolin, 10 parts of calcined high-alumina powder, 10 parts of quartz, and 23 parts of potassium feldspar are respectively placed in a ball mill for wet ball milling to remove iron. After passing through a 120 sieve, the ball-milled raw materials are mixed, and 15 parts of modified mullite whiskers and 0.4 parts of polyvinyl alcohol are added. According to the ratio of ball to material of 10:1, the ball milling mixing is continued for 0.5h, and the grinding slurry is separated and placed in an environment of 105±5℃ for drying until the water content in the slurry drops to 8%;
[0030] Wherein, the preparation method of the modified mullite whisker is:
[0031] a. After washing the mullite whiskers with deionized water for 3 times, drying to constant weight, placing them in a planetary ball mill, ball milling for 5 minutes at a ball-to-material ratio of 10:1, separating the ground mullite whiskers and dispersing them in a sodium hydroxide solution with a pH value of 11.5-12, with a solid-liquid ratio of 1:20, heating to 95°C, ultrasonically shaking for 90 minutes, centrifuging the mullite whiskers, washing them with boiling deionized water for 3 times, and then dispersing the mullite whiskers in KH550 again, with a solid-liquid ratio of 1:10, heating to 75°C, ultrasonically shaking for 0.5h, adding 20% deionized water by volume of KH550, continuing to stir and react for 3h, centrifuging the mullite whiskers, and vacuum drying to constant weight to obtain pre-treated mullite whiskers;
[0032] b. Place the micro-nano glass powder in a planetary ball mill, according to a ball-to-material ratio of 15:1, ball milling treatment for 10 minutes, separate the activated micro-nano glass powder after grinding, place it in KH560, the solid-liquid ratio is 1: (5, heat to 75-85 ° C, ultrasonic vibration dispersion for 0.5h, add 20% of the volume of KH560 deionized water, continue stirring and reacting for 3h, centrifuge to separate the micro-nano glass powder, vacuum evaporate to constant weight, and obtain pre-treated micro-nano glass powder;
[0033] c. Disperse 10 parts of pre-treated mullite whiskers in deionized water at a solid-liquid ratio of 1:8 by weight, stir and mix for 25 minutes, add 2 parts of pre-treated micro-nano glass powder, stir and ultrasonically shake for 0.5-1h, heat to 85-95°C, stir and react for 1h, spray dry, collect the dried product, and obtain modified mullite whiskers;
[0034] S2. The dried raw material was stirred and mixed again at a rate of 100 rpm for 1 h, and then atomized deionized water was evenly sprayed into the raw material 3 times. The total amount of atomized deionized water was 5% of the mass of the dried raw material. After spraying, the raw material was left to stand for 6 h;
[0035] S3. After the aged raw materials are pressed into shape, the pressing pressure is 12MPa. After pressing and forming, the green body is placed in a mold, a pressure of 15MPa is applied to the green body and the temperature is raised to 105℃. After keeping warm and drying for 1h, the dried green body is transferred to a calcining furnace, and the green body is heated to 850℃ at a rate of 2℃ / min. After keeping warm for 20min, the temperature is raised to 1150℃, kept warm for 40min, and then heated to 1300-1350℃ again. After keeping warm and calcining for 13h, it is cooled to 750℃ at a rate of 0.5℃ / min. After keeping warm for 60min, it is cooled to 450℃ at a rate of 0.5℃ / min again. After keeping warm for 30min, it is cooled to room temperature with the furnace temperature. The calcination is completed to obtain high hardness scratch-resistant tiles.
[0036] Embodiment 2. A method for preparing a high-hardness scratch-resistant tile comprises the following steps:
[0037] Compared with Example 1, the present embodiment increases the amount of modified mullite whiskers added;
[0038] S1. According to the weight percentage, 50 parts of kaolin, 10 parts of calcined high alumina powder, 10 parts of quartz, and 23 parts of potassium feldspar are respectively placed in a ball mill for wet ball milling to remove iron. After passing through a 120 sieve, the ball-milled raw materials are mixed, and 25 parts of modified mullite whiskers and 0.4 parts of polyvinyl alcohol are added. According to the ratio of ball to material of 10:1, the ball milling mixing is continued for 0.5h, and the grinding slurry is separated and placed in an environment of 105±5℃ for drying until the water content in the slurry drops to 8%;
[0039] Wherein, the preparation method of the modified mullite whisker is:
[0040] a. After washing the mullite whiskers with deionized water for 3 times, drying to constant weight, placing them in a planetary ball mill, ball milling for 5 minutes at a ball-to-material ratio of 10:1, separating the ground mullite whiskers and dispersing them in a sodium hydroxide solution with a pH value of 11.5-12, with a solid-liquid ratio of 1:20, heating to 95°C, ultrasonically shaking for 90 minutes, centrifuging the mullite whiskers, washing them with boiling deionized water for 3 times, and then dispersing the mullite whiskers in KH550 again, with a solid-liquid ratio of 1:10, heating to 75°C, ultrasonically shaking for 0.5h, adding 20% deionized water by volume of KH550, continuing to stir and react for 3h, centrifuging the mullite whiskers, and vacuum drying to constant weight to obtain pre-treated mullite whiskers;
[0041] b. Place the micro-nano glass powder in a planetary ball mill, according to a ball-to-material ratio of 15:1, ball milling treatment for 10 minutes, separate the activated micro-nano glass powder after grinding, place it in KH560, the solid-liquid ratio is 1: (5, heat to 75-85 ° C, ultrasonic vibration dispersion for 0.5h, add 20% of the volume of KH560 deionized water, continue stirring and reacting for 3h, centrifuge to separate the micro-nano glass powder, vacuum evaporate to constant weight, and obtain pre-treated micro-nano glass powder;
[0042] c. Disperse 10 parts of pre-treated mullite whiskers in deionized water at a solid-liquid ratio of 1:8 by weight, stir and mix for 25 minutes, add 2 parts of pre-treated micro-nano glass powder, stir and ultrasonically shake for 0.5-1h, heat to 85-95°C, stir and react for 1h, spray dry, collect the dried product, and obtain modified mullite whiskers;
[0043] S2. The dried raw material was stirred and mixed again at a rate of 100 rpm for 1 h, and then atomized deionized water was evenly sprayed into the raw material 3 times. The total amount of atomized deionized water was 5% of the mass of the dried raw material. After spraying, the raw material was left to stand for 6 h;
[0044] S3. After the aged raw materials are pressed into shape, the pressing pressure is 12MPa. After pressing and forming, the green body is placed in a mold, a pressure of 15MPa is applied to the green body and the temperature is raised to 105℃. After keeping warm and drying for 1h, the dried green body is transferred to a calcining furnace, and the green body is heated to 850℃ at a rate of 2℃ / min. After keeping warm for 20min, the temperature is raised to 1150℃, kept warm for 40min, and then heated to 1300-1350℃ again. After keeping warm and calcining for 13h, it is cooled to 750℃ at a rate of 0.5℃ / min. After keeping warm for 60min, it is cooled to 450℃ at a rate of 0.5℃ / min again. After keeping warm for 30min, it is cooled to room temperature with the furnace temperature. The calcination is completed to obtain high hardness scratch-resistant tiles.
[0045] Embodiment 3. A method for preparing a high-hardness scratch-resistant tile, comprising the following steps:
[0046] Compared with Example 1, this example increases the amount of pre-treated micro-nano glass powder added in step c;
[0047] S1. According to the weight percentage, 50 parts of kaolin, 10 parts of calcined high-alumina powder, 10 parts of quartz, and 23 parts of potassium feldspar are respectively placed in a ball mill for wet ball milling to remove iron. After passing through a 120 sieve, the ball-milled raw materials are mixed, and 15 parts of modified mullite whiskers and 0.4 parts of polyvinyl alcohol are added. According to the ratio of ball to material of 10:1, the ball milling mixing is continued for 0.5h, and the grinding slurry is separated and placed in an environment of 105±5℃ for drying until the water content in the slurry drops to 8%;
[0048] Wherein, the preparation method of the modified mullite whisker is:
[0049] a. After washing the mullite whiskers with deionized water for 3 times, drying to constant weight, placing them in a planetary ball mill, ball milling for 5 minutes at a ball-to-material ratio of 10:1, separating the ground mullite whiskers and dispersing them in a sodium hydroxide solution with a pH value of 11.5-12, with a solid-liquid ratio of 1:20, heating to 95°C, ultrasonically shaking for 90 minutes, centrifuging the mullite whiskers, washing them with boiling deionized water for 3 times, and then dispersing the mullite whiskers in KH550 again, with a solid-liquid ratio of 1:10, heating to 75°C, ultrasonically shaking for 0.5h, adding 20% deionized water by volume of KH550, continuing to stir and react for 3h, centrifuging the mullite whiskers, and vacuum drying to constant weight to obtain pre-treated mullite whiskers;
[0050] b. Place the micro-nano glass powder in a planetary ball mill, according to a ball-to-material ratio of 15:1, ball milling treatment for 10 minutes, separate the activated micro-nano glass powder after grinding, place it in KH560, the solid-liquid ratio is 1: (5, heat to 75-85 ° C, ultrasonic vibration dispersion for 0.5h, add 20% of the volume of KH560 deionized water, continue stirring and reacting for 3h, centrifuge to separate the micro-nano glass powder, vacuum evaporate to constant weight, and obtain pre-treated micro-nano glass powder;
[0051] c. Disperse 10 parts of pre-treated mullite whiskers in deionized water at a solid-liquid ratio of 1:8 by weight, stir and mix for 25 minutes, add 4 parts of pre-treated micro-nano glass powder, stir and ultrasonically shake for 0.5-1h, heat to 85-95°C, stir and react for 1h, spray dry, collect the dried product, and obtain modified mullite whiskers;
[0052] S2. The dried raw material was stirred and mixed again at a rate of 100 rpm for 1 h, and then atomized deionized water was evenly sprayed into the raw material 3 times. The total amount of atomized deionized water was 5% of the mass of the dried raw material. After spraying, the raw material was left to stand for 6 h;
[0053] S3. After the aged raw materials are pressed into shape, the pressing pressure is 12MPa. After pressing and forming, the green body is placed in a mold, a pressure of 15MPa is applied to the green body and the temperature is raised to 105℃. After keeping warm and drying for 1h, the dried green body is transferred to a calcining furnace, and the green body is heated to 850℃ at a rate of 2℃ / min. After keeping warm for 20min, the temperature is raised to 1150℃, kept warm for 40min, and then heated to 1300-1350℃ again. After keeping warm and calcining for 13h, it is cooled to 750℃ at a rate of 0.5℃ / min. After keeping warm for 60min, it is cooled to 450℃ at a rate of 0.5℃ / min again. After keeping warm for 30min, it is cooled to room temperature with the furnace temperature. The calcination is completed to obtain high hardness scratch-resistant tiles.
[0054] Embodiment 4. A method for preparing a high-hardness scratch-resistant tile, comprising the following steps:
[0055] Compared with Example 1, this embodiment increases the treatment time of the sodium hydroxide solution in step a;
[0056] S1. According to the weight percentage, 50 parts of kaolin, 10 parts of calcined high-alumina powder, 10 parts of quartz, and 23 parts of potassium feldspar are respectively placed in a ball mill for wet ball milling to remove iron. After passing through a 120 sieve, the ball-milled raw materials are mixed, and 15 parts of modified mullite whiskers and 0.4 parts of polyvinyl alcohol are added. According to the ratio of ball to material of 10:1, the ball milling mixing is continued for 0.5h, and the grinding slurry is separated and placed in an environment of 105±5℃ for drying until the water content in the slurry drops to 8%;
[0057] Wherein, the preparation method of the modified mullite whisker is:
[0058] a. After washing the mullite whiskers with deionized water for 3 times, drying to constant weight, placing them in a planetary ball mill, ball milling for 5 minutes at a ball-to-material ratio of 10:1, separating the ground mullite whiskers and dispersing them in a sodium hydroxide solution with a pH value of 11.5-12, with a solid-liquid ratio of 1:20, heating to 95°C, ultrasonically shaking for 150 minutes, centrifuging the mullite whiskers, washing them with boiling deionized water for 3 times, and then dispersing the mullite whiskers again in KH550 with a solid-liquid ratio of 1:10, heating to 75°C, ultrasonically shaking for 0.5 hours, adding 20% deionized water by volume of KH550, continuing to stir and react for 3 hours, centrifuging the mullite whiskers, and vacuum drying to constant weight to obtain pre-treated mullite whiskers;
[0059] b. Place the micro-nano glass powder in a planetary ball mill, according to a ball-to-material ratio of 15:1, ball milling treatment for 10 minutes, separate the activated micro-nano glass powder after grinding, place it in KH560, the solid-liquid ratio is 1: (5, heat to 75-85 ° C, ultrasonic vibration dispersion for 0.5h, add 20% of the volume of KH560 deionized water, continue stirring and reacting for 3h, centrifuge to separate the micro-nano glass powder, vacuum evaporate to constant weight, and obtain pre-treated micro-nano glass powder;
[0060] c. Disperse 10 parts of pre-treated mullite whiskers in deionized water at a solid-liquid ratio of 1:8 by weight, stir and mix for 25 minutes, add 2 parts of pre-treated micro-nano glass powder, stir and ultrasonically shake for 0.5-1h, heat to 85-95°C, stir and react for 1h, spray dry, collect the dried product, and obtain modified mullite whiskers;
[0061] S2. The dried raw material was stirred and mixed again at a rate of 100 rpm for 1 h, and then atomized deionized water was evenly sprayed into the raw material 3 times. The total amount of atomized deionized water was 5% of the mass of the dried raw material. After spraying, the raw material was left to stand for 6 h;
[0062] S3. After the aged raw materials are pressed into shape, the pressing pressure is 12MPa. After pressing and forming, the green body is placed in a mold, a pressure of 15MPa is applied to the green body and the temperature is raised to 105℃. After keeping warm and drying for 1h, the dried green body is transferred to a calcining furnace, and the green body is heated to 850℃ at a rate of 2℃ / min. After keeping warm for 20min, the temperature is raised to 1150℃, kept warm for 40min, and then heated to 1300-1350℃ again. After keeping warm and calcining for 13h, it is cooled to 750℃ at a rate of 0.5℃ / min. After keeping warm for 60min, it is cooled to 450℃ at a rate of 0.5℃ / min again. After keeping warm for 30min, it is cooled to room temperature with the furnace temperature. The calcination is completed to obtain high hardness scratch-resistant tiles.
[0063] Comparative Example 1. A method for preparing high-hardness scratch-resistant tiles, comprising the following steps:
[0064] Compared with Example 1, this comparative example did not add the prepared modified mullite whiskers;
[0065] S1. According to the weight percentage, 50 parts of kaolin, 10 parts of calcined high alumina powder, 10 parts of quartz, and 23 parts of potassium feldspar are respectively placed in a ball mill for wet ball milling to remove iron. After passing through a 120 sieve, the ball-milled raw materials are mixed, and 0.4 parts of polyvinyl alcohol are added. According to the ratio of ball to material of 10:1, the ball milling mixing is continued for 0.5h, and the grinding slurry is separated and placed in an environment of 105±5℃ for drying until the water content in the slurry drops to 8%;
[0066] S2. The dried raw material was stirred and mixed again at a rate of 100 rpm for 1 h, and then atomized deionized water was evenly sprayed into the raw material 3 times. The total amount of atomized deionized water was 5% of the mass of the dried raw material. After spraying, the raw material was left to stand for 6 h;
[0067] S3. After the aged raw materials are pressed into shape, the pressing pressure is 12MPa. After pressing and forming, the green body is placed in a mold, a pressure of 15MPa is applied to the green body and the temperature is raised to 105℃. After keeping warm and drying for 1h, the dried green body is transferred to a calcining furnace, and the green body is heated to 850℃ at a rate of 2℃ / min. After keeping warm for 20min, the temperature is raised to 1150℃, kept warm for 40min, and then heated to 1300-1350℃ again. After keeping warm and calcining for 13h, it is cooled to 750℃ at a rate of 0.5℃ / min. After keeping warm for 60min, it is cooled to 450℃ at a rate of 0.5℃ / min again. After keeping warm for 30min, it is cooled to room temperature with the furnace temperature. The calcination is completed to obtain high hardness scratch-resistant tiles.
[0068] Comparative Example 2. A method for preparing high-hardness scratch-resistant tiles, comprising the following steps:
[0069] Compared with Example 1, the mullite whiskers were not modified in this comparative example;
[0070] S1. According to the weight percentage, 50 parts of kaolin, 10 parts of calcined high alumina powder, 10 parts of quartz, and 23 parts of potassium feldspar are respectively placed in a ball mill for wet ball milling to remove iron. After passing through a 120 sieve, the ball-milled raw materials are mixed, and 15 parts of mullite whiskers and 0.4 parts of polyvinyl alcohol are added. According to the ratio of ball to material of 10:1, the ball milling mixing is continued for 0.5h, and the grinding slurry is separated and placed in an environment of 105±5℃ for drying until the water content in the slurry drops to 8%;
[0071] S2. The dried raw material was stirred and mixed again at a rate of 100 rpm for 1 h, and then atomized deionized water was evenly sprayed into the raw material 3 times. The total amount of atomized deionized water was 5% of the mass of the dried raw material. After spraying, the raw material was left to stand for 6 h;
[0072] S3. After the aged raw materials are pressed into shape, the pressing pressure is 12MPa. After pressing and forming, the green body is placed in a mold, a pressure of 15MPa is applied to the green body and the temperature is raised to 105℃. After keeping warm and drying for 1h, the dried green body is transferred to a calcining furnace, and the green body is heated to 850℃ at a rate of 2℃ / min. After keeping warm for 20min, the temperature is raised to 1150℃, kept warm for 40min, and then heated to 1300-1350℃ again. After keeping warm and calcining for 13h, it is cooled to 750℃ at a rate of 0.5℃ / min. After keeping warm for 60min, it is cooled to 450℃ at a rate of 0.5℃ / min again. After keeping warm for 30min, it is cooled to room temperature with the furnace temperature. The calcination is completed to obtain high hardness scratch-resistant tiles.
[0073] Testing: The ceramic tiles prepared in Examples 1-4 and Comparative Examples 1-2 were prepared into ceramic tile samples of 300*300*8 mm, and the wear resistance of the samples prepared in Examples 1-4 and Comparative Examples 1-2 was tested according to GB / T 3810-2016 "Test Methods for Ceramic Tiles"; the flexural strength of the samples prepared in Examples 1-4 and Comparative Examples 1-2 was tested according to GB / T 2542-2012;
[0074] The samples prepared in Examples 1-4 and Comparative Examples 1-2 were tested for Mohs hardness using a Mohs hardness tester. The test results are shown in the following table.
[0075] Wear-resistant revolutions Flexural strength(MPa) Mohs hardness scale Example 1 16500 64.5 4 Example 2 >17500 68.4 5 Example 3 17000 66.9 4 Example 4 17000 66.7 4 Comparative Example 1 13500 55.1 4 Comparative Example 2 15500 48.2 4
[0076] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-hardness anti-scratch tile, characterized by: The high-hardness anti-scratch ceramic tile comprises 45-55 parts of kaolin, 5-12 parts of calcined high-alumina powder, 10-15 parts of quartz, 20-23 parts of potassium feldspar, 15-25 parts of modified mullite whiskers, and 0.15-0.4 parts of polyvinyl alcohol in parts by weight; Wherein, the preparation method of the modified mullite whisker is: a. Wash the mullite whiskers with deionized water for 3-5 times, dry them to constant weight, place them in a planetary ball mill, and ball-mill them for 5 minutes at a ball-to-material ratio of (8-12):
1. Separate the milled mullite whiskers and disperse them in a sodium hydroxide solution. Heat to 95°C, ultrasonically shake for 90-150 minutes, centrifuge to separate the mullite whiskers, wash them with boiled deionized water for 3-5 times, and disperse them again in KH550 at a solid-liquid ratio of 1:(10-25). Heat to 75-85°C, ultrasonically shake for 0.5-1h, add 20% deionized water by volume of KH550, continue stirring for 2-5h, centrifuge to separate the mullite whiskers, and vacuum dry to constant weight to obtain pre-treated mullite whiskers; The pH value of the sodium hydroxide solution is 11.5-12; The solid-liquid ratio of the mullite whisker to the sodium hydroxide solution is 1:(8-50); b. Place the micro-nano glass powder in a planetary ball mill, and mill it for 10-15 minutes at a ball-to-material ratio of (15-20):
1. Separate the activated micro-nano glass powder and place it in KH560 at a solid-liquid ratio of 1:(5-15). Heat it to 75-85°C, disperse it by ultrasonic vibration for 0.5-1.5 hours, add deionized water that is 20% of the volume of KH560, continue stirring and reacting for 2-4 hours, centrifuge and separate the micro-nano glass powder, and evaporate it in vacuum to constant weight to obtain pre-treated micro-nano glass powder; The particle size of the micro-nano glass powder is 1500-8000 mesh; c. Disperse the pre-treated mullite whiskers into deionized water with a solid-liquid ratio of 1: (5-10), stir and mix for 15-25 minutes, add the pre-treated micro-nano glass powder, stir and ultrasonically shake for 0.5-1h, heat to 85-95℃, stir and react for 0.5-1.5h, spray dry, collect the dried product, and obtain modified mullite whiskers; The mass ratio of the pre-treated mullite whiskers to the pre-treated micro-nano glass powder is 10:(2-4).
2. The high-hardness anti-scratch ceramic tile according to claim 1, characterized in that: In step a, the mullite whisker has a diameter of 0.2-3 μm and a length of 5-200 μm.
3. A method for preparing a high-hardness anti-scratch tile according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Wet-mill kaolin, calcined high-alumina powder, quartz and potassium feldspar in a ball mill to remove iron. After passing through a 120-200 sieve, mix the milled raw materials, add modified mullite whiskers and polyvinyl alcohol, and continue to ball-mill for 0.5 hours at a ball-to-material ratio of 10:
1. Separate the ground slurry and dry it in an environment of 105±5℃ until the water content in the slurry drops to 5-10%; S2. After the dried raw material is stirred and mixed again at a rate of 50-200rpm for 0.5-1h, the raw material is evenly sprayed with atomized deionized water 3-5 times. After the spraying is completed, the raw material is left to stand for 4-8h; S3. After the aged raw materials are pressed into shape, the green body is placed in a mold, the temperature is raised to 105-110°C under pressure, and after drying for 1-2 hours, the dried green body is transferred to a calcining furnace and calcined to obtain high-hardness scratch-resistant tiles.
4. The method for preparing a high-hardness scratch-resistant tile according to claim 3, characterized in that: In step S2, the total amount of the atomized deionized water is 5-8% of the mass of the raw material after drying.
5. The method for preparing a high-hardness scratch-resistant tile according to claim 3, characterized in that: In step S3, the pressing pressure is 10-15 MPa; When maintaining pressure and heating, the applied pressure is 12-15MPa.
6. The method for preparing a high-hardness scratch-resistant tile according to claim 3, characterized in that: In step S3, when the green body is calcined after drying, the parameters are as follows: The green body is heated to 850-900°C at a rate of 1.5-3°C / min, kept warm for 20-30min, then heated to 1150-1200°C, kept warm for 40-60min, heated to 1300-1350°C again, kept warm for 13-16h, cooled to 750-800°C at a rate of 0.5°C / min, kept warm for 30-70min, cooled to 400-500°C at a rate of 0.5°C / min again, kept warm for 30-40min, cooled to room temperature along with the furnace temperature, and the calcination is completed.
Citation Information
Patent Citations
Modified cordierite porous ceramic material and preparation method and application thereof
CN110294637A
Energy-saving high-hardness ceramic tile and production process thereof
CN114671677A
Cited By
Whisker-toughened mullite ceramic and method for making the same
CN122831678A